The quality of the rural library service in Malaysia: the views of the rural community - Omar, Siti Zobidah; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva; Samsuddin, Samsul Farid; Mazuki, Raidah; Mohamed Shaffril, Hayrol Azril (Medwell Journals, 2016)
The present study aims to identify the quality of the rural library service in Malaysia. The study is qualitative in nature whereby the data were gathered via three focus group discussions. In general, the data reflect that the majority of rural library services are delivered to the rural community to a high quality. Nevertheless, there are some issues such as a lack of updated educational materials, internet connection and signage as well as lack of interests among young users that need to be taken into consideration. A number of discussions have been highlighted which it is hoped will assist those concerned in constructing strategies to further enhance the quality and effectiveness of Malaysia’s rural library services.